Drosophila melanogaster White Mutant w1118 Undergo Retinal Degeneration - Ferreiro, María José; Pérez, Coralia; Marchesano, Mariana; Ruiz, Santiago; Caputi, Angel; Aguilera, Pedro; Barrio, Rosa; Cantera, Rafael (Frontiers in Neuroscience, 2018)
Key scientific discoveries have resulted from genetic studies of Drosophila melanogaster, using a multitude of transgenic fly strains, the majority of which are constructed in a genetic background containing mutations in the white gene. Here we report that white mutant flies from w1118 strain undergo retinal degeneration. We observed also that w1118 mutants have progressive loss of climbing ability, shortened life span, as well as impaired resistance to various forms of stress. Retinal degeneration was abolished by transgenic expression of mini-white+ in the white null background w1118. We conclude that beyond the classical eye-colour phenotype, mutations in Drosophila white gene could impair several biological functions affecting parameters like mobility, life span and stress tolerance. Consequently, we suggest caution and attentiveness during the interpretation of old experiments employing white mutant flies and when planning new ones, especially within the research field of neurodegeneration and neuroprotection. We also encourage that the use of w1118 strain as a wild-type control should be avoided.